Structure of Polymorphic Stomata in Canella winterena (L.) Geartn. (Canellaceae). Issue 4 (6th February 2014) - Mandal, Manasi; Mitra, Sonia; Maity, D.
Abstract: The presence of 10 types of normal stomata along with 4 subtypes, one intermediate type between stephanocytic and hemiparacytic and some abnormal stomatal structures both in the vegetative and floral organs of Canella winterena (L.) Geartn. (Canellaceae) is reported here. The epidermal cells are polygonal, isodiametric in surface view with straight anticlinal walls. The stomata are amphibrachyparacytic, anomocytic, anisocytic, brachyparacytic, brachyparatetracytic, cyclocytic, hemiparacytic, laterocytic, holoparacytic, stephanocytic, one intermediate type between stephanocytic and hemiparacytic, etc. Abnormalities like contiguous stomata, different types of twin stomata and cytoplasmic bridge between adjacent stomata, stomata with single guard cell, single guard cell with pore juxtaposed with normal stoma are also found. The presence of giant stomata is a significant finding. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)